Pengarusutamaan Moderasi Beragama; Potret Peran Eks Napi Teroris di Surabaya - Setiyawan, Imas (JOM, 2024)
Religious moderation is a government program that aims to shape the character of a tolerant society, so that an atmosphere of peaceful and harmonious religious life is built, this is certainly the basis for religious life and a heterogeneous state. Therefore, the role of every element of society becomes urgent in the program of strengthening religious moderation, one of which is the role of ex-terrorist Convicts. This research seeks to see and analyze more deeply the role of the former ex-terrorist Convicts in grounding the attitude of religious moderation as well as socializing the dangers of radicalism in society. By using a qualitative approach, accompanied by interview techniques, observation and documentation, this research will focus on former ex-terrorist Convicts in the city of Surabaya as the object of research. The results showed that the former ex-terrorist Convicts used two ways in strengthening religious moderation, namely first, strengthening the role through his duties as a speaker at social, academic and community forums in collaboration with other parties such as BNPT, BIN and the Ministry of Religion. Second, strengthening the counter-radicalism narrative through books written as a source in understanding the importance of tolerant life in religion.